7p=8(2p+9)

Simple and best practice solution for 7p=8(2p+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p=8(2p+9) equation:


Simplifying
7p = 8(2p + 9)

Reorder the terms:
7p = 8(9 + 2p)
7p = (9 * 8 + 2p * 8)
7p = (72 + 16p)

Solving
7p = 72 + 16p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-16p' to each side of the equation.
7p + -16p = 72 + 16p + -16p

Combine like terms: 7p + -16p = -9p
-9p = 72 + 16p + -16p

Combine like terms: 16p + -16p = 0
-9p = 72 + 0
-9p = 72

Divide each side by '-9'.
p = -8

Simplifying
p = -8

See similar equations:

| 6x+3=39whatisx | | 2x+2x-50=490 | | 5.1075+x=0.15(56.75+x) | | 2x+2x+25=490 | | 6x-6(y-3x)-7y= | | (4a^3-4c^2)/2a-c=0 | | 2w-2(-7x+6w)-4x= | | k(2000)=1108+(265+5.8-33) | | 5x+7=32linear | | 3m^2-4m-2=0 | | 8r+8=56 | | 5(-2w-3z)-6(-6z+w)= | | 4(x^2+4x+4)+320=0 | | x=sqrtx+7+5 | | x^2-6x+9=-21 | | x^2-6x+9=-23 | | 4x(5x+1)=-x(7-x) | | 6(2x-4)+3(5-x)-9=9(x-2) | | -8x-7/7=11 | | 1/5t-1/8=5/8 | | 24-x=3/2 | | 6x-8y-x+2y= | | k(calories)=1108+(w+h-a) | | y=3x^2+9x+1 | | k=1108+(w+h-a) | | -1/3+t=-2.5 | | 3.4x=2.4x+6.0 | | 2.6+x=8.9 | | 14x-(8x-3)=51 | | 5(x+5)+10=10x-5(x-4) | | 39=-3(23-b)+3(b-2) | | 2(6z+4)-9=83 |

Equations solver categories